2021
DOI: 10.1016/j.ygeno.2020.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide SNP discovery from Darjeeling tea cultivars - their functional impacts and application toward population structure and trait associations

Abstract: Genotyping by sequencing and identification of functionally relevant nucleotide variations in crop accessions are the key steps to unravel genetic control of desirable traits. In the scope of present work, elite cultivars of Darjeeling tea were undergone SNP genotyping by doubledigest restriction site associated DNA sequencing method. This study reports a set of 54,206 high-quality SNP markers discovered from ~10.4 GB sequence data, encompassing 15 chromosomes of reference tea genome. Genetic relatedness among… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Several recent studies have used a GWAS approach to explore major genes associated with several important specialized metabolites. Hazra et al (2020) conducted a GWAS analysis of 23 Darjeeling tea cultivars and identified 12 SNPs related to epigallocatechin gallate (EGCG), 8 SNPs related to flavonoids, 8 SNPs related to flavor, and 3 SNPs related to phenolics [ 16 ]. Zhang et al (2020) conducted a GWAS on the catechin trait of 176 ancient tea plant accessions and revealed that the CsANR , CsF3′5′H , and CsMYB5 genes may affect tea plant catechin content [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have used a GWAS approach to explore major genes associated with several important specialized metabolites. Hazra et al (2020) conducted a GWAS analysis of 23 Darjeeling tea cultivars and identified 12 SNPs related to epigallocatechin gallate (EGCG), 8 SNPs related to flavonoids, 8 SNPs related to flavor, and 3 SNPs related to phenolics [ 16 ]. Zhang et al (2020) conducted a GWAS on the catechin trait of 176 ancient tea plant accessions and revealed that the CsANR , CsF3′5′H , and CsMYB5 genes may affect tea plant catechin content [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of mass spectrometry (MS) platforms and sequencing technology, metabolome-based genome-wide association studies (mGWAS) has been successfully applied to exploit natural genotypic variation and identify metabolic quantitative trait loci (mQTL) responsible for metabolomic variation in humans (Hagenbeek et al, 2020;Qin et al, 2012;Zhang et al, 2015), animals (Hartiala et al, 2016) This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. (Alseekh et al, 2018;Francisco et al, 2016;Slaten et al, 2020;Wang et al, 2021b;Wen et al, 2014;Zhu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The diverse tea genetic resources, coupled with metabolite detection methodologies, enable the identification of mQTL which would further lead to better understanding of the natural variation of metabolites in tea plant. However, previous studies using tea germplasm to map mQTL have merely been pursued on a handful of metabolites or inadequate genotypic data (Fang et al ., 2021 ; Hazra et al ., 2021 ; Huang et al ., 2022 ; Yamashita et al ., 2020 ; Yu et al ., 2020 ; Zhang et al ., 2020b , 2021 ). As such a large‐scale combined metabolomics and population genetics study in tea research can yield significant insights into the genetic and metabolic landscape of tea chemical diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Genotypic variation is one of the key factors by which the plant can differentially respond to a particular environmental stimuli 11 . In tea, challenges remained viable to explore the genetic diversity underlying varying physiological response to environment 12,13 . This study aimed to explore natural variations in the ecophysiological traits within seasons and the corresponding multifaceted biochemical responses given by the gene pool of 22 tea cultivars.…”
mentioning
confidence: 99%